Exploring Social Media to Improve Students’ Writing Skills at Tertiary Level - Azizah Septi Istikhori; Muamaroh Muamaroh (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
In the digital era, integrating social media into language learning has become increasingly important to address students’ writing challenges and align instructional practices with their technological realities. This study aims to explore how social media can be used to improve students’ writing skills at the tertiary level. A qualitative descriptive research design was employed to examine students’ experiences in using social media. The participants were 54 university students enrolled in the Short Functional Text course at Universitas Muhammadiyah Surakarta, with 25 students purposively selected for semi-structured interviews. Data were collected through online questionnaires and interviews, while triangulation was applied to ensure validity. The data were analyzed using thematic analysis to identify social media platforms used, reasons for usage, as well as perceived advantages and disadvantages. The findings indicate that students most frequently used Instagram, TikTok, Twitter/X, WhatsApp, and Duolingo. These platforms were chosen due to ease of access, practicality, and the availability of abundant learning content. The main benefits included improved writing skills, increased confidence, flexible learning opportunities, access to reliable resources, and enhanced vocabulary. However, students also faced challenges such as distractions, poor internet connection, low confidence in English ability, and decreased grammar and spelling accuracy.